MAKING MEANING THROUGH TEACHER TALK: LEXICAL RELATIONS IN VOCABULARY INSTRUCTION IN AN ESP SPEAKING CLASSROOM - Novi Indriyani; Dian Agustina Purwanto Wakerkwa (PT Akselerasi Karya Mandiri, 2026)
Vocabulary mastery remains one of the most persistent challenges for EFL learners, particularly when closely related words carry different meanings across registers, a problem that intensifies in register-dense professional genres. This qualitative study aims to identify the types of lexical relations used by an English for Specific Purposes (ESP) speaking teacher while clarifying vocabulary for her students, and to describe the discourse strategies accompanying those clarifications. A case study design was employed, with the ESP teacher and her speaking class of undergraduate Law students preparing curriculum vitae (CV) and job-interview materials as the research subject. Data were collected through a 100-minute non-participant classroom observation, video recording, and a semi-structured interview, then analyzed using qualitative descriptive analysis. Consistent with this aim, the results show that the teacher's talk fully realized seven of the eight categories of lexical relations proposed by Yule (2020), namely synonymy, antonymy, hyponymy, prototype effects, polysemy, metonymy, and collocation, while the eighth category, homophones and homonyms, was only partially represented through two instances of homonymy, with no instances of homophones identified in the data. These relations were embedded within a recurring routine of elicitation, code-switching, contrastive restatement, and exemplification. These findings imply that a single, register-dense ESP topic can be strategically leveraged to teach a wide range of lexical relations. It is concluded that explicit, context-sensitive vocabulary clarification supports learners' precision of meaning in specialized professional communication.